Incumbent competition and private agenda - Go, Anne Marie L. (Animo Repository, 2020)
Consider two politicians who decide whether to follow what they believe the electorate wants or choose the option that secures their private gain. Policies are implemented when the politicians reach a unanimous decision. The electorate only rewards a politician when a policy is implemented, or when the politician is the only one whose action coincides with the popular decision. I find that if the politicians have good decision-making abilities, sufficiently high payoffs in policy implementation given moderate private agenda payoffs pushes the politicians to implement the popular policy. For very poor decision-making abilities, at sufficiently high policy rewards, I find that they vote for the same action to implement a policy regardless of what the electorate want - converging to a decision that neither provides them with a private benefit nor follows exactly the popular decision. For issues of very high relevance to the electorate, only popular policies are passed.